ChemInform Abstract: Three New Hasubanan Alkaloids from Stephania hernandifolia (WILLD.) WALP. Issue 11 (18th March 2014) - Tang, Li‐Jia; Deng, Lu‐Lu; He, Li; Song, Shao‐Hui; Zhang, Jian‐Xin; Hao, Xiao‐Jiang; Zhang, Yuan‐Hu
Abstract isolation, structure and cytotoxicity of three new hasubanan alkaloids, hernsubanines A—C